The Effects of Impervious Surface Area, Tree Canopy Cover, and Floral Richness on Bee Abundance, Richness, and Diversity Across an Urban Landscape - Gerner, Eden (Université d'Ottawa / University of Ottawa, 2020)
As urbanization increases globally, habitat loss is increasing at an unprecedented rate, eroding the suitability of many landscapes for most forms of wildlife, including bees. At least some of this habitat loss is through the ongoing expansion of urban areas, a process termed ‘urbanization’. Studies of the effects of urbanization and urban land use on bees have reported a mixture of results, including some instances where at least some species appear to do better in urban areas than they do in lands surrounding urban areas. While the impacts of urbanization on bee communities has been investigated, tree canopy cover has been largely overlooked as a contributor to urban bee distributions, despite their potential importance as a predictor of bee activity. I investigated the impacts of urban land use and tree canopy cover on bee communities across a variety of neighbourhoods in a medium-sized Canadian city (Ottawa, Ontario). In total, I surveyed bee communities in 27 residential yards that varied in terms of the degree of urban land use (measured as percent impervious surface area) and tree canopy cover (percent deciduous canopy cover) across a range of spatial scales. Using linear regression and model selection, I determined that bee abundance was negatively correlated with the degree of urban land use surrounding a yard, and positively correlated with the richness of the local (i.e., yard) flowering plant community. Yard floral richness, but not urban land use or tree cover, was also a predictor of the diversity of the bee community visiting the yard. In fact, tree canopy cover did not factor in any of the top models predicting either bee abundance, richness, or diversity. My results support the idea that urban land use could negatively impact bee communities, but also suggest that landscaping and urban planning decisions that maximize local floral richness could counteract some of the negative impacts of urbanization on bee populations.
Keywords: Wild Bees; Pollinators; Urban; Tree Cover